Meningocele in Cattle (Bos taurus). Technical note - Cardenas-Cruz, Jimena Marynes; Membrillo-Vargas, Esmerita Yulisa; Portal-Torres, Jorge; Cueva-Rodríguez, Medali (Revista Científica de la Facultad de Ciencias Veterinarias, 2025)
Miningocele is the protrusion of the membranes of the brain or spinal cord due to a defect that is generated in the skull or spinal column, like a small protruding wet sac. Malformations in animals may be caused by environmental, genetic, infectious agents, ingestion of toxic plants or inheritance of recessive genes. A case of meningocele in a bovine is reported in the Pathology Laboratory of the Faculty of Veterinary Sciences of the National University of Cajamarca. In the clinical specimen a protrusion was observed in the cranial part, which presented cerebrospinal fluid. The objective is to identify a pathology in a cattle. A 4-month-old male cattle fetus was reported. As a result of the macroscopic inspection, it was identified as a case of cattle meningocele, due to the presence of a sac-like protrusion in the brain. It was concluded that the pathology was a bovine meningocele.